Iterative closed-loop identification of MIMO systems using ARX-based Leaky Least Mean Square Algorithm - Rahim, M.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Closed-loop identification of MIMO systems is considered. An iterative Leaky Least Mean Squares (LLMS) algorithm is proposed for the development of ARX structure. The performance of the proposed algorithm with respect to the existing recursive algorithms is investigated in a simulation study. The simulation results show that the proposed algorithm can produce more accurate parameter estimates than the conventional recursive algorithms. Â© 2014 IEEE.